Bioprospecting of enzymes from fungi isolated from Canastra cheeses for industrial application - Lopes, Isabelle Lima (2022)
The microbial diversity of Brazilian artisanal cheeses is far from being fully explored. Among frequently isolated microorganisms, bacteria and fungi stand out. Filamentous fungi can be highlighted for their significant impact in the quality of surface mould-ripened cheeses, besides that several metabolites produced, including enzymes. Fungal enzymes are widely used in industry, due to the easier extraction and purification compared to other enzymes sources. In this context, the aim of this study was to evaluate the proteolytic and lipolytic activity of 58 filamentous fungi isolated from artisanal cheeses produced in Canastra region, Minas Gerais State, Brazil. Submerged fermentation assays were performed considering casein as a protease inducer and olive oil as a lipase-inducing substrate. The proteolytic activity was evaluated by the caseinolytic method using a spectrophotometric assay; lipolytic activity, by potentiometric titration of fatty acids released by fungi lipases. Penicillium steckii and Aspergillus versicolor showed the highest proteolytic activity, with with 31.14 U/mL and 29.35 U/mL, respectively. Regarding lipolytic activity, Geotrichum candidum and Penicillium steckii presented the highest activities, with 62.91 U/mL and 55.44 U/mL, respectively. Considering the results of the proteolytic activity and their potential use in the dairy industry, a Geotrichum candidum isolate (GC-31) was selected and submitted to ultraviolet light (UV) mutation induction assay; then, the mutants obtained were evaluated for proteolytic activity. In total, 18 mutant strains were obtained; GC-M10 showed an increase in proteolytic activity up to 274% (29.96 U/mL) in comparison to the wild type (10.94 U/mL); therefore, the UV induction method was efficient in increasing the enzymatic activity of the isolated evaluated. This study showed that fungi isolated from artisanal cheeses produced in Canastra region have potential for biotechnological exploration and the production of industrial enzymes. Keywords: Protease.Lipase. Canastra cheese.Geotrichum candidum.Mutante.Epifluorescence microscopy.